Analisis Kuantitatif Cemaran Logam Merkuri pada Obat Bahan Alam Sediaan Padat yang Beredar di Propinsi Bali - Putu Wahyu Diantari; Wanda Indriani Wibowo; Rabiati Rabiati; Prakhas Adhitya JS (Eruditio : Indonesia Journal of Food and Drug Safety, 2025)
Herbal Medicines (OBA) are widely used as complementary or alternative treatments globally. Their popularity stems from the perception that they are natural, accessible, and have fewer side effects than synthetic drugs. However, high demand raises concerns regarding heavy metal contamination (As, Cd, Pb, Hg), which can occur through soil absorption, manufacturing, or intentional addition. This study analyzed Mercury (Hg) levels in solid OBA across Bali. Samples collected from various traditional medicine depots were tested using microwave digestion and atomic absorption spectroscopy (AAS). Results showed that 108 out of 214 samples—primarily in powder form—contained detectable Mercury. Nevertheless, these concentrations remained below official safety thresholds, with results ranging from 0.02 to 0.16 ppm. Based on the risk evaluation through the Estimated Daily Intake (EDI) indicator with a range of results of 2.86 x 10-6 - 2.29 x 10-5, Target Hazard Quotient (THQ) of 0.01 - 0.08, and Cancer Risk (CR), with a value of 2.43 x 10-11 - 1.94 x 10-10 it can be concluded that the OBA solid dosage forms sampled in Bali Province in 2025 are safe for consumption.